Barsbay Döneminde Mısır’da Beşerî Olayların ve Doğal Felaketlerin Toplum ve İktisadî Hayat Üzerinde Etkileri 1422–1438 - Gökhan, İlyas (Fırat University, 2007)
Bu çalışma, Memlûk sultanlarından Barsbay döneminde 1422–1438 meydana gelen iktisadî buhran ve veba salgınları hakkındadır. Bu dönemde devlet siyasî bakımdan güçlü olmasına rağmen iktisadî açıdan zayıftı. Bu zayıflığın sebepleri idarecilerin yanlış politikalar takip etmelerinin yanında bu süreçte ortaya çıkan kıtlıklardır. İdareciler, iktisadî olaylara müdahale edip, tekelciliğe başvurmuşlardır. Bu durum, ülkenin hem iç hem de dış ticaretini kötü şekilde etkilenmiştir. Nil’in akış düzenin yıllarda farklılık göstermesi ekonomiyi kötü etkiledi. Buna ilaveten Mısır parası istikrarsızdı. İnsanlar fiyatların yüksekliğinden ve enflasyondan sıkıntı çektiler

This work is about plagues and economic crisis took place during the reign of Barsbay one sultans of Memluk State 1422–1438 . In this period, altough the state was politically strong, it was economically poor. The reasons for economic weakness was the wrong policies the rulers followed and droughts that occurred in this period. The rulers internevened in economic affairs, and established monopolies in many economic activitics. This case effected the domestic badly, as well as the foreign merchants. Nile’s low currents in different years had bad effects on the economy. In addition, Egypyie’s money was not stable. The people were suffering from high pricies and enflation. Furthermore, in this period Egypts suffered from many plagues
During the Reign of Barsbay Impacts of Natural Disaster and Human Activities on the Society Economic Life in Egypt. 1422–1438